2017
DOI: 10.5194/acp-17-2279-2017
|View full text |Cite
|
Sign up to set email alerts
|

Observations and model simulations of snow albedo reduction in seasonal snow due to insoluble light-absorbing particles during 2014 Chinese survey

Abstract: Abstract. A snow survey was carried out to collect 13 surface snow samples (10 for fresh snow, and 3 for aged snow) and 79 subsurface snow samples in seasonal snow at 13 sites across northeastern China in January 2014. A spectrophotometer combined with chemical analysis was used to quantify snow particulate absorption by insoluble light-absorbing particles (ILAPs, e.g., black carbon, BC; mineral dust, MD; and organic carbon, OC) in snow. Snow albedo was measured using a field spectroradiometer. A new radiative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(111 citation statements)
references
References 104 publications
7
104
0
Order By: Relevance
“…A wide range of values has been reported by different authors for BC concentrations in snow and ice samples from different regions (Table S2). The concentrations of BC in our samples were higher than those reported by many authors (Table S2) but were comparable with the results reported by Xu et al (2012) in the Tien Shan, by Li et al (2016) in the northeast of the Tibetan Plateau, by Wang et al (2017) in northern China, and by Zhang et al (2017) in western Tien Shan, central Asia. High concentrations indicate high deposition rates on the snow and ice surface, but there are several possible reasons for a wide variation in values apart from differences in deposition rates, including differences in sampling protocols, geographical/sampling location and elevation of sampling site (Qu et al, 2014), and year/season of sampling.…”
Section: Bc Oc and Dust Concentrationssupporting
confidence: 90%
“…A wide range of values has been reported by different authors for BC concentrations in snow and ice samples from different regions (Table S2). The concentrations of BC in our samples were higher than those reported by many authors (Table S2) but were comparable with the results reported by Xu et al (2012) in the Tien Shan, by Li et al (2016) in the northeast of the Tibetan Plateau, by Wang et al (2017) in northern China, and by Zhang et al (2017) in western Tien Shan, central Asia. High concentrations indicate high deposition rates on the snow and ice surface, but there are several possible reasons for a wide variation in values apart from differences in deposition rates, including differences in sampling protocols, geographical/sampling location and elevation of sampling site (Qu et al, 2014), and year/season of sampling.…”
Section: Bc Oc and Dust Concentrationssupporting
confidence: 90%
“…The grain nonsphericity effect can be even larger if considering the same snow volume/mass (equivalently R v ) rather than effective size (R e ) (see section 3.4). Wang et al (2017) found that the spectrally (0.4-1.4 μm) averaged albedos of spherical snow grains are lower than those of hexagonal plates and fractal grains by 0.008 and 0.017, respectively, based on the AART theory (Kokhanovsky & Zege, 2004). Dang et al (2016) (5) and (6) Observations (e.g., Dominé et al, 2003, Erbe et al, 2003 suggest that Koch snowflakes and spheroids could be used to mimic fresh and aged snow, respectively.…”
Section: 1002/2017jd027752mentioning
confidence: 99%
“…While the mean OC concentration in surface aged snow and granular ice was 2090 ± 568 ng g À1 and 4304 ± 358 ng g À1 , respectively. BC and OC deposited on the snow and glaciers were widely considered as insoluble light-absorbing impurities (ILAIs) (Wang et al, 2017;Niu et al, 2018). ILAIs combined with WSOC in snow and glacier can be defined as lightabsorbing matter (LAM), which considerably reduces snow spectral albedo, absorbs large amount of solar energy, and accelerates the retreat of glaciers.…”
Section: Properties Of Wsoc In Glaciersmentioning
confidence: 99%